Competency-Based Video Conferencing Education Suite (CoViCES) - Ling, Siew Eng; Kit Yok, Margaret; Engkamat, Adeline; Goh, Kelvin Tee Hiong (2025)
The Competency-Based Video Conferencing Education Suite (CoViCES) addresses the challenges of synchronous online and hybrid teaching, which became critical during the COVID-19 pandemic and remain relevant in the digital education era. Existing video conferencing platforms often lack pedagogical integration, hindering engagement and effective online teaching. CoViCES offers a comprehensive solution through innovations on: a) Video Conferencing Toolkits combining technology with pedagogical best practices, b) Open Educational Resources (OERs) on both technical and instructional aspects for virtual classroom, c) Competency matrices outlining key digital and pedagogical skills required for effective participation in virtual classrooms, d) self-assessment tools to evaluate proficiency, track progress, and identify areas for improvement, and e) a reproducible Educator Training Workshop Model for scalable implementation. Developed through Design Thinking methodology, CoViCES follows an iterative, user-centered process which empathizes with stakeholders, defining challenges, ideating solutions, prototyping toolkits, and testing them in realworld educational settings across Asia and Europe. This approach ensures that the solutions are practical, context-sensitive, and pedagogically robust. The novelty of innovations includes culturally adaptive toolkits that address regional teaching practices and technological constraints, competency frameworks specifically designed for synchronous video-based learning, filling a critical gap in digital education standards, and Sustainable training models that empower educators to become effective online instructors and trainers. Aligned with SDG 4 (Quality Education) and SDG 10 (Reduced Inequalities), CoViCES enhances digital teaching efficiency, student engagement, and institutional readiness for hybrid learning. Short-term impacts include improved local practices, while long-term sustainability is ensured through open-access resources, institutional integration, and global dissemination.